Diagnosis and management of idiopathic pulmonary fibrosis. Issue 7 (20th July 2022) - Joshi, Vijay; Nagji, Zaneeta
Abstract : Idiopathic pulmonary fibrosis (IPF) is a form of idiopathic interstitial pneumonia that currently carries a poor prognosis and remains incurable, though antifibrotic therapy can slow disease progression. This article provides an overview of its diagnosis, treatment and the management of co‐morbidities.